Sistem Informasi Penjualan Rumah Pada Green Golf Residence Kota Jambi - Surizkiyana, Surizkiyana; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2021)
PT. Rendy Utama Karya in storing data on house sales at Green Golf Residence, Jambi city, is still in the form of documents or archives, resulting in obstruction in the production of sales reports which hinders company performance. The purpose of this study is to analyze the home sales information system at Green Golf Residence Jambi City and design a home sales information system for Green Golf Residence Jambi City using object-oriented methods with UML (Unified Modeling Language tools). The conclusion of the analysis and design of this sales system is that This new system will be able to reduce the problem of delays in information obtained, and it is hoped that the need for information on sudden home sales data reports can be fulfilled properly, quickly and accurately. The advice is to support systems that have been designed for the need for human resources and facilities. which is good to support the implementation of the system so that it can run well